Optimizing Elementary Student Learning Outcomes through Differentiated Instruction Based on Learning Styles - Ariesta, Freddy Widya (Universitas Pendidikan Ganesha, 2025)
This study examines how differentiated instruction based on learning styles can help optimize elementary school students' learning outcomes in IPAS subjects. Through a quasi-experimental method with a pretest-post-test control group design, the study involved 49 grade V students who were divided into experimental and control groups. Students' learning styles were identified using the VARK (Visual, Auditory, Read/Write, Kinesthetics) instrument, then the appropriate learning strategies were applied. The results showed that students in the experimental group experienced significantly higher learning outcomes than the control group. The paired sample T-test resulted in a significance value of <0.001, and the N-gain score reached 0.719 (high category). In addition, the distribution of learning outcomes improvement showed that most experimental group students were in the high improvement category. This finding shows that when students learn according to the way of learning that they understand best, the results are much more optimal. Differentiated instruction is proven to not only improve students' grades but also help them learn more comfortably and meaningfully. This research confirms that differentiated instruction based on students' learning styles is essential for improving learning outcomes in elementary education.